Direct immunofluorescence in Lupus Erythematosus (LE) - Isfer, Roseli Svartman (1996)
One hundred and twenty-six patients with LE were studied. They were distributed as follows: 84 with DLE, 13 with SALE and 29 with SLE. Biopsies from the skin lesions were performed and submitted to DIE Positive results were equal to 69, 61.5 and 72.4 percent of the DLE, SALE and SLE cases, respectively. These data are in accordance with the literature. IgM was the most frequently found immunoglobulin, followed by the association IgM+C3.